Exosomes define a local and systemic communication network in healthy pancreas and pancreatic ductal adenocarcinoma - Bárbara Adem; Nuno Bastos; Carolina F. Ruivo; Sara Sousa-Alves; Carolina Dias; Patrícia F. Vieira; Inês A. Batista; Bruno Cavadas; Dieter Saur; José C. Machado; Dawen Cai; Sonia A. Melo (Nature Communications, 2024)
Abstract Pancreatic ductal adenocarcinoma (PDAC), a lethal disease, requires a grasp of its biology for effective therapies. Exosomes, implicated in cancer, are poorly understood in living systems. Here we use the genetically engineered mouse model (ExoBow) to map the spatiotemporal distribution of exosomes from healthy and PDAC pancreas in vivo to determine their biological significance. We show that, within the PDAC microenvironment, cancer cells establish preferential communication routes through exosomes with cancer associated fibroblasts and endothelial cells. The latter being a conserved event in the healthy pancreas. Inhibiting exosomes secretion in both scenarios enhances angiogenesis, underscoring their contribution to vascularization and to cancer. Inter-organ communication is significantly increased in PDAC with specific organs as most frequent targets of exosomes communication occurring in health with the thymus, bone-marrow, brain, and intestines, and in PDAC with the kidneys, lungs and thymus. In sum, we find that exosomes mediate an organized intra- and inter- pancreas communication network with modulatory effects in vivo.